Autism spectrum disorder and Coffin–Siris syndrome—Case report - Milutinovic, Luka; Grujicic, Roberto; Mandic Maravic, Vanja; Joksic, Ivana; Ljubomirovic, Natasa; Pejovic Milovancevic, Milica (Frontiers in Psychiatry, 2023)
Introduction: Autism spectrum disorders (ASD) are a group of developmental disorders characterized by deficits in social communicative skills and the occurrence of repetitive and/or stereotyped behaviors. Coffin-Siris syndrome (CSS) is classically characterized by aplasia or hypoplasia of the distal phalanx or nail of the fifth and additional digits, developmental or cognitive delay of varying degree, distinctive facial features, hypotonia, hirsutism/hypertrichosis, and sparse scalp hair. In this report, we present a detailed description of autistic traits in a boy diagnosed with CSS and further discuss their genetic backgrounds. Case description: An 8-year-old boy with ASD, congenital anomalies, and neurological problems had been diagnosed with Coffin-Siris syndrome after genetic testing. Genetic testing revealed a heterozygous de novo pathogenic variant (class 5) c.1638_1647del in the ARID1B gene that is causative of Coffin-Siris syndrome, but also other intellectual disability (ID)-related disorders including autism. Tests that preceded the diagnoses, as well as congenital anomalies and developmental issues, were further described in an attempt to better present his phenotype. Conclusion: Both autism and ARID1B-related disorder are on a spectrum. This report points out the importance and necessity of further research regarding these disorders' genetic background to understand their complex etiology.